Guatemala : Selected Issues and Analytical Notes. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper estimates potential output growth and the output gap for Guatemala. Potential output growth averaged 4.4 percent just before the global financial crisis but has since declined to 3.75 percent owing to lower capital accumulation and total factor productivity (TFP) growth. It is estimated at 3.8 percent in 2016, and the output gap has virtually closed. Potential growth is expected to reach 4 percent in the medium term owing to the expected improvements in TFP growth. Policies should also prioritize mobilizing domestic savings to invest and build a higher capital stock.